Rеopening the administrative procedure - Lončar, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The new General Administrative Procedure Act of 2016 introduced a number of innovations in the system of extraordinary legal remedies. From the aspect of legal protection of the parties, the most should have been expected from the changes regarding the Reopening since it is an extraordinary legal remedy, which is by far the most commonly used in administrative practice, due to its existence of process material that was unknown during the conducting of the process. However, the legal regime of this extraordinary remedy has only slightly changed. The basic changes concerns the reasons for the reopening, the time limits within which it can be used, and the circle of entities legally legitimized for filing a reopening. Regarding the reasons for reopening, as the most important element of the legal regime, only minor linguistic corrections were made and only two new reasons were added, due to which the administrative procedure in Serbia today can be reopened even if the Constitutional Court of the Republic of Serbia is in the same administrative matter, the constitutional complaint, found a violation or denial of the human or minority rights and freedoms guaranteed by the Constitution, while not annulling the impugned decision, as well as if the European Court of Human Rights subsequently found in the same administrative matter that rights or freedom of the applicant are violated or denied. Due to the inadequately set objective deadline for filing a Reopening Procedure, which is inappropriately short for this type of reason, the practical importance of prescribing these two new Reopening procedure grounds is greatly diminished. In addition, by omitting the Public Prosecutor, the circle of entities legally legitimized for the Reopening is reduced only to the party from the administrative procedure and the administrative body that issued the final administrative act, which can be repeated ex officio, which in no way contributes, not only to improvement legal protection of the parties to the proceedings, but also the possibility of achieving a greater degree of objective legality in resolving administrative matter.